Place Attachment in Public Space Case Study: Hiraq Square Lhokseumawe, Aceh – Indonesia - Karsono, Bambang; Novianti, Yenny; ., Nurhaiza; Masthura Hassan, Soraya (International Journal of Engineering and Technology, 2019)
Concerning to the issue of place attachment, the research tends to observes the functional attachment which will affect the level of attachment in Hiraq Square Lhokseumawe (HSL), a renowned public space among local people in the city of Lhokseumawe, Aceh, Indonesia. Place attachment is known as a process to unite people and specific space that can encourage the sense of place. It is also indicating the interrela-tion between physical features and its function, by this process the sense of a place can be emerged. These concepts concentrate on the phys-ical features and activities together with the meanings affected by users that will establish the meaning and the identity of the place. The re-search is conducted by applying indirect method to simplify ordinary patterns and people-particular patterns of the place. Overall, 120 re-spondents at certain area of HSL were questioned through questionnaire survey and 10 kiosk operators were questioned. The findings indi-cates that the people have a robust relationship with the local environment and appoint the significance of place as economicsâ€™ dependence and recreational place. The level of functional attachment to HSL is range from level 1 to level 3, whereas level 3 implicates a higher en-gagement in loyalty, goals and obedience to the environment.Â